Chondrosarcoma, A 30 Year Retrospective Study in Cancer Institute Imam Khomeini Hospital and Faculty of Dentistry of Tehran University of Medical Sciences - N. Eshghyar; Mohebbi (Tehran University of Medical Sciences, 2004)
Statement of Problem: Chondrosarcoma is a tumor which includes 10 percent of the bone primary tumors. Its prevalence is half of the osteosarcoma and two times of Ewing's. The mean age of the patients ranges between 30-50 years of old. There is no significant sex or race predilection. The most common complaint is the presence of a painless and enlarging mass. Its clinical course is described as slow-growing lesion with local invasion and recurrence, no or delayed metastasis, almost long survival. Purpose: The aims of this study were as follows: the determination of prevalence of reported Chondrosarcoma in cancer institute Imam Khomeini hospital and faculty of dentistry of Tehran University of medical sciences, comparison of jaw Chondrosarcoma to the body one, evaluation of sex, age, clinical and histological parameters and prevalence of different locations in body. Materials and Methods: In this study the biopsy notes of all kinds of chondrosarcoma of the body in cancer institute (212 cases) and the extracted files of the patients with the jaws chondrosarcoma in cancer institute and department of oral pathology of faculty of dentistry, University of Tehran medical sciences (23 Cases) were evaluated. Results: In this retrospective statistical study the proportion of the patients with the jaws conventional chondrosarcoma to the patients with conventional Chondrosarcoma of the body was 8.57%. The mean age of the total patients and the patients with jaws chondrosarcoma were 36.21 and 38.87 years, respectively. Men were somehow more involved. Pelvic was the most common location of the tumor. Maxilla involvement was 3-4 times more than mandible. Microscopic manifestation and tumor grading suggested a low grade lesion in jaws. Local recurrence in jaws was 33.3%. Conclusion: The most common site of involvement of chondrosarcoma was pelvic and maxillary involvement was more common than mandible. Its prevalence was in the posterior site of the jaws.